Long-term outcome after surgical and endovascular management of true and false subclavian artery aneurysms. (June 2014) - Zehm, Sarah; Chemelli, Andreas; Jaschke, Werner; Fraedrich, Gustav; Rantner, Barbara
Subclavian artery aneurysm is a rare but serious disease due to the risk of thrombosis, embolization, rupture and compression of adjacent structures. Treatment consists of surgical and endovascular techniques. Up to now few long-term follow-up results have been reported. In our study the results from 15 patients treated for subclavian artery aneurysms were evaluated. Eleven patients underwent open surgical reconstruction, four patients were treated endovascularly. After a mean follow-up period of 77 months (83 months for the open surgical group, 38 months for the endovascular group), 10 of 11 open surgical reconstructions and all primarily implanted stent grafts were patent. Secondary intervention was necessary in two patients. Thirty-day mortality for both treatment groups was 0%. Subclavian artery aneurysm-related symptoms disappeared in six out of 10 patients after the treatment. Long-term outcomes with good technical results, patency rates and low periprocedural morbidity could be shown in both treatment groups.